Avaliação do potencial de degradação do herbicida diuron por fungos isolados de solo de canavial e suas tolerâncias aos metabólitos gerados - Perissini, Bruna Nogueira [UNESP] (2015)
Degraded ecosystems recovery is one of the current challenges, which implies the development of effective methodologies that minimize the damage and not interfere with natural bioprocesses. Bioremediation is a technology that utilizes living organisms and/or their derivatives to eliminate or reduce the pollutant levels in an environment. The use of fungi for biodegradation of xenobiotics of various chemical groups has been extensively explored, due to its biological and morphological characteristics, and their extracellular enzymes. The action of a microorganism on the pollutant compound is desired in order to reduce its chemical complexity, however, the generation of more toxic intermediate compounds than the original may occur, requiring the evaluation of these metabolite derivatives prior to infer the use of a determined bioremediation technique. This work aimed to evaluate the herbicide diuron degradation by Trichoderma harzianum G15, T. virens F28, Cunninghamella elegans B06, Fusarium sp. B19, Aspergillus sp. G25, A. brasiliensis G08, Beauveria sp. 211 e Mortierella alpina F17 and evaluate their tolerance and ability to metabolize those generated metabolites. T. harzianum G15, T. virens F28 and C. elegans B06 were able to degrade between 12 and 43% of diuron and accumulated in the culture medium DCPMU metabolites and DCPU but not 3,4-DCA. When grown in medium containing these metabolites to replace diuron, no inhibitory effect on the growth of fungi and the degradation of DCPMU was 42 to 73%, for DCPU from 37 to 69%, for 3,4-DCA from 15 to 100%, and for diuron 19 to 84%. The formation of different metabolites from 3,4-DCA, such as 3,4-CAC and 3,4-DCNB indicated that the fungi have different enzymatic mechanisms of biodegradation of such a compound. The metabolites detected in culture media allowed to suggest that diuron degradation followed the degradation following sequence: DCPMU, DCPU, 3,4-DCA, 4-CAC, CAC 3.4-and 3.4-DCNB. The...